Intelligent real-time traffic signal control based on a paraconsistent logic program EVALPSN - Nakamatsu, K.; Seno, T.; Abe, J. M.; Suzuki, A.; Wang, G. Y.; Liu, Q.; Yao, Y. Y.; Skowron, A. (Springer, 2003)
In this paper, we introduce an intelligent real-time traffic signal control system based on a paraconsistent logic program called an EVALPSN (Extended Vector Annotated Logic Program with Strong Negation), that can deal with contradiction and defeasible deontic reasoning. We show how the traffic signal control is implemented in EVALPSN with taking a simple intersection example in Japan. Simulation results for comparing EVALPSN traffic signal control to fixed-time traffic signal control are also provided.
Keywords: traffic signal control; paraconsistent logic program; intelligent control; defeasible deontic reasoning